STABILITY AND ADAPTABILITY OF EXPERIMENTAL DOUBLE HYBRIDS IN CORN - da SILVA, Ricardo Machado; ROSSE, Leonardo Novaes; MÔRO, José Roberto (Scientia Agraria, 2002)
The interaction genotype-environment represent one of the most important complications in genetic improvement programs, difficulting the evaluation and advise of genetics materials with good phenotypical stability. The objective of this work was to study the phenotypical stability of double experimental corn hybrids by means of the Additive Main Effects and Multiplicative Interaction Analysis (AMMI) models. For this purpose 124 double experimental hybrids were evaluated plus 5 double commercial hybrids as controls. These hybrids were divided in 4 essay groups (6x6) with 3 repeats and installed in three different environments of the State of São Paulo (Brazil): JAB-1 and JAB-2 in Jaboticabal, during the months of December in 1995 and January in 1996, respectively, and BAR-1 in Barretos in December, 1995. We were able to conclude that the model was usefull for to detect significant differences in the behaviour of the genetics materials, even using a small number of environments. These environments were, quite different, and contributed a lot for the significance of the scores. In a situation where there are only few environments, the AMMI model seems to be very adequate for this kind of studies.